PENERAPAN DASAR-DASAR MANAJEMEN PENDIDIKAN ISLAM (MPI) DALAM PENGELOLAAN DISIPLIN SANTRI DI PESANTREN AZZAKIYYAH KABUPATEN BANDUNG - Nurdita Indriawati; Mulyawan Safwandy Nugrah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study discusses in depth how the basic principles of Islamic Education Management (MPI) are applied in regulating and fostering discipline among students at the Azzakiyyah Islamic Boarding School in Cileunyi, Bandung Regency. This research emerged from observations that, despite the existence of regulations, the level of student compliance varied, indicating that successful discipline depends on a management system capable of effectively fostering internalization of values. Unlike previous studies that generally focus on technical dimensions, this research aims primarily to analyze the application of the four principles of MPI (planning, organizing, implementing, and supervising) while revealing the Islamic philosophical and spiritual foundations that underpin the entire management process. The method chosen is qualitative with a phenomenological research type, conducted at PP Azzakiyyah in October 2025. The research subjects (leaders, mentors, and students) were determined using purposive sampling techniques. Primary data were collected through in-depth interviews and participatory observation, then analyzed using Miles and Huberman's interactive model, with validity reinforced through source and method triangulation. Key findings show that discipline management is implemented holistically and transcends the boundaries of the conventional management framework (P-O-A-C). Specifically, the principle of planning is based on al-Maslahah al-Mursalah (public interest) and is ratified through the syura (consultative) mechanism. Organization is imbued with the concept of amanah (responsibility). In practice, consistent enforcement of rules is combined with spiritual guidance (muhasabah an-nafs) to trigger internal discipline awareness based on muraqabah (awareness of being watched by God). Finally, supervision places the tarbiyah (guidance) program as a follow-up to sanctions, which is based on rahmatan lil alamin (mercy). The scientific novelty of this study lies in the verification that MPI successfully bridges the technical aspects of management with the spiritual-philosophical dimensions, with the consistency of the leadership in providing uswah hasanah (good example) being the main supporting factor for its success.